Plantar fibrolipomatous hamartoma in a patient with neurofibromatosis type 1. - Singh, S.; Kowe, P.; Sawatkar, G.; Meshram, N. (European Journal of Pediatric Dermatology, 2025)
A female in her early teens presented with freckles over her face and axilla, dental pits, and a progressive swelling over the medial aspect of the right foot. The swelling looked like a plexiform neurofibroma, but histopathology revealed a rare variant of lipoma, a fibro-lipomatous hamartoma of the median plantar nerve.